Teachers’ Strategies in Improving the Effectiveness of Learning for Children with Special Needs at SLB Pelita Hati Pekanbaru - Delva Syara; Cici Murni; Ayu Widiawati; Rika Fitri Ramadani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The effectiveness of learning for children with special needs (CSN) is influenced by teachers’ strategies in adapting instruction to students’ characteristics and learning abilities. This study aims to analyze teachers’ strategies in improving learning effectiveness for children with special needs at SLB Pelita Hati Pekanbaru. The study employed a descriptive qualitative approach using interviews, observations, and documentation involving school principals and teachers as key informants. The findings show that teachers implemented adaptive strategies such as differentiated instruction, individualized approaches, repetitive teaching techniques, and the use of visual and concrete learning media to support students’ understanding. Learning assessment was conducted flexibly based on students’ individual progress. In addition, collaboration between teachers and parents became an important factor in supporting learning continuity at home. However, challenges remained in terms of limited learning media, technology integration, and systematic documentation of student development. Overall, teachers’ strategies at SLB Pelita Hati Pekanbaru contributed positively to improving learning effectiveness for children with special needs, although continuous professional development and instructional innovation are still needed.